Anti-CCP antibody and rheumatoid factor concentrations predict greater disease activity in men with rheumatoid arthritis. Issue 7 (3rd May 2010) - Miriovsky, Benjamin J; Michaud, Kaleb; Thiele, Geoffrey M; O'Dell, James R; Cannon, Grant W; Kerr, Gail; Richards, J Steuart; Johnson, Dannette; Caplan, Liron; Reimold, Andreas; Hooker, Roderick; Mikuls, Ted R
Abstract : Objective: To examine associations of anti-cyclic citrullinated peptide (aCCP) antibody and rheumatoid factor (RF) concentrations with future disease activity in men with rheumatoid arthritis (RA). Methods: Outcome measures were examined in male US veterans with RA and included (1) proportion of observations in remission (disease activity score (DAS28) ≤2.6); (2) remission for ≥3 consecutive months; and (3) area under the curve (AUC) for DAS28. The associations of autoantibody concentration (per 100 unit increments) with outcomes were examined using multivariate regression. Results: 826 men with RA were included in the analysis; the mean (SD) age was 65 (10.5) years and follow-up was for 2.6 (1.3) years. Most were aCCP (75%) and RF (80%) positive. After multivariate adjustment, aCCP (OR 0.93; 95% CI 0.89 to 0.96) and RF concentrations (OR 0.92; 95% CI 0.90 to 0.94) were associated with a lower odds of remission, a lower proportion of observation in remission (p=0.017 and p=0.002, respectively) and greater AUC DAS28 (p=0.092 and p=0.007, respectively). Among patients with discordant autoantibody status, higher concentrations of both aCCP and RF trended towards an inverse association with remission (OR 0.93; 95% CI 0.83 to 1.05 and OR 0.80; 95% CI 0.59 to 1.10, respectively). Conclusions: Higher aCCP concentrations (particularly in RF-positive patients) are associated with increased disease activity in US veterans with RA, indicating that aCCP concentration is predictive of future disease outcomes in men.